Gen Z's Perception of Understanding Tax Compliance Behavior (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2024)
This study examinesthe factors influencing tax compliance among Generation Z in Solo Raya, Indonesia, with a particular focus on the challenges of low compliance within the informal sector. Employing a quantitative approach, data were gathered through closed questionnaires distributed to 135 respondents and analyzed using Structural Equation Modeling -Partial Least Squares(SEM-PLS) via SmartPLS 3. The results revealthat reference groups and tax knowledge have a significant positive impacton tax compliance, whereas thedigitalization ofthe tax system and social media donot demonstratea significant effect. Thesefindings underscore the critical role of social influence and tax education in improving compliance while indicating that digitalization efforts and social media campaigns require further refinement. This research contributesto the development of effective government policies aimed at enhancing tax compliance among Generation Zthrough targeted educational initiatives and the strategic application of technology.